Energy Assessment of the State of Pipe Column in the Deep Well Drilling - Volchenko, D.A.; Miralamov, H.F.; Bоlonniy V.T.; Savchin, M.V.; Malyk, V.Ya.; Savchin, Ya.M. (Herald of Azerbaijan Engineering Academy, 2022)
The paper studies the technological features of drilling and the compressed air expulsion, and a generalized assessment of the heat balance of pipe column in drilling well. An algorithm of the nonequilibrium thermodynamics with the linear regimes of energy loading of the pipe column during a well drilling is considered. A computational analysis is performed with the following initial data: D=0.28 m; d=0.155 m; tp=48°С; t1=23.6°С; t2=35.3°C; thermal conductivity coefficients: rocks λ1=2.56 W/(m∙°С); and steel pipe of the column λ2 and λ3 = 60 W/(m ∙°С); the heat transfer coefficient from the ascending and outgoing flows of the washing liquid are 175 W/(m∙°C) and 256 W/(m∙°C). In this case, the average linear heat transfer coefficient is 220 W/(m2∙°C). An algorithm for estimating the heat balance of the drill column and its annulus during their interaction with humidified compressed air is proposed. When the well is purged with compressed air, the average linear heat transfer coefficient is 95 W/(m2∙°C); the bulk temperature gradient for mud at the bottom of a 100 m long drill string was 0.03 °C/m. From the above parameters, the ratios are formed that are equal to the Onsager and Saxen ratios, which makes it possible to determine the parameters by calculation.